Intervention of Peer Groups in Strengthening Youth Religious Character Based on Art Activities Rebbana - Zaenullah Zaenullah; Rosyida Nurul Anwar (International Journal on Advanced Science, Education, and Religion, 2021)
Ideally, students should receive education not only at school, but also from family and community. Because children are part of society, they are more in the environment where they live. Thus, intervention to strengthen religious character also needs to be carried out by all parties, including the youth community such as religious arts club. The purpose of this study is how peers intervene in strengthening religious characters based on art activity using tambourine. This research method uses descriptive qualitative. Data collection techniques in this study were carried out through participatory observation (as both observer and participant), in-depth interviews (deep interviews), and documentation. The data analysis of this research uses the Miles and Huberman model. Data analysis takes place when data collection is carried out and after data collection for a certain period that cannot be determined. The data analysis includes data reduction (data reduction), data display (data presentation), and conclusion drawing/verification (drawing conclusions/verification). The results showed that the intervention to strengthen religious character was focused on art-based religious activities which were carried out programmatically could create a good environment for the fulfillment of inner experiences from religious practice. This also act as a strategy to minimize youth activities that do not give any benefits for themselves and their social environment. The approach used is a value-planting approach and an action approach. Keywords: Religious Character, Strengthening Religious Character, Degradation Moral